The Common Thread of the Paradigm of Motives for Social Action and Discursive Traditions in Looking at the Success Rate of Arab Spring Social Movements in Egypt and the Kingdom of Saudi Arabia in 2010-2012 - Hakam*, Muhammad Ahsanul; Muttaqin, Mohammad Izdiyan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Arab Spring Phenomenon is an important incident that more and less affected Middle East Region. Nevertheless, there is something different between the countries on the output. There is country who more affected like Egypt. And there is country who less affected like The Kingdom of Saudi Arabia. How that two country can be so different will be faced by the two paradigm, Social Action Motives by Max Weber and Discursive Tradition by Talal Asad through comparative method. Furthermore, a research message can be meaningful. Because of that, the research is ontological, epistemology, and axiology. What is the red threads essence within the two paradigm? How the paradigm answers the phenomenon? What can be learned from the research?.